FRI0373 Assessing patients that continue to flare despite apparent optimal urate lowering therapy. (23rd January 2014) - Khanna, D.; Hagerty, D.; Mischler, R.; Morlock, R.
Abstract : Background: Gout is a common inflammatory arthritis and its worldwide prevalence is increasing. Effective treatments are approved to lower serum urate levels, reduce the burden of uric acid and thereby eliminating flares and decreasing tophi. Objectives: To describe physician, patient and treatment characteristics in those patients who are considered "controlled" by their physician with xanthine oxidase (XO) inhibitor therapy, despite having 2 or more flares per year. Methods: Data were assessed from a survey of US physicians about gout disease management. Patient results were confirmed through in-depth chart audits assessing diagnosis, comorbid conditions, disease severity and laboratory assessments. Disease severity was measured using a physician global assessment (mild, moderate or severe), flare counts, joint damage and presence of tophi. Type and dose of XO inhibitor, length of current treatment, compliance, physician type and patient socio-demographics factors were identified. XO inhibitor control was defined using a 10 point physician assigned score with higher scores indicating more control ("Do you consider this patient to be well controlled on their current urate lowering therapy, where control means there is no desire to increase the dose to achieve better control?"). Patients with a score of ≥7/10 were classified as "controlled". Multivariate and descriptive statistics were used to describe patients having more than 2 flares per year (excluding treatment initiation flares) where physicians reported "no desire to increase dose" of the current ULT. Results: Physicians interviewed included 125 rheumatologists and 124 primary care physicians. Of the 1245 patients with gout, 81% were male and the average age was 57 (sd=13). 858 (69%) patients were treated with a XO inhibitor of which 278 (32%) patients classified as controlled but experienced 2 or more flares in the last year. Patients defined as controlled and reporting 2 or more flares a year had higher sUA compared to patients classified as controlled and having less than 2 flares a year (7.0 vs. 6.4 mg/dL; p<.01). Likewise these patients were more likely to have tophi (30% vs. 18%; p<0.01). A backward stepwise multivariate model predicting patients classified as controlled and continuing to flare (2+ flares in the last year) found chart documented co-existing kidney disease (OR 2.4; p<0.01), alcoholism (OR 2.4; p<0.01) and depression (OR 1.8; p<0.05) to be associated with higher flares. Additionally, treatment with anti-hyperglycemic agents (OR 1.6; p<0.05) and physician identified tophi (OR 1.6; p<0.05) also predicted perceived control in patients with 2 or more flares in the last year. Conclusions: Despite patients being considered controlled, 32% continued to have ≥2 flares per year. These patients are more likely to have kidney disease and other comorbid conditions. Current treatment options for these patients may not be sufficient to adequately control gout flares. Disclosure of Interest: D. Khanna Grant/Research support from: Ardea Biosciences, NIH, Consultant for: Savient, Novartis, Takeda, Speakers Bureau: Savient, D. Hagerty Employee of: Ardea Biosciences, R. Mischler Employee of: Ardea Biosciences, R. Morlock Employee of: Ardea Biosciences